Contribution and Effectiveness of Hotel Tax Revenue in Yogyakarta City, 2017-2021 - Budiherwanto, Iwan; Rohmah, Tri Nur; Putri, Nurwana Cendana (Journal of Economics and Public Health, 2023)
Hotel tax for tourism areas such as the City of Yogyakarta is an important component in the source of local revenue generation. The purpose of this research is to analyze the effectiveness of hotel tax, see the trend, analyze the contribution of hotel tax to tourism sector revenue and PAD and identify efforts to optimize hotel tax in the city of Yogyakarta. This study uses a quantitative descriptive research method by relying on secondary and primary data from the Badan Pengelolaan Keuangan dan Aset daerah (BPKAD) of the City of Yogyakarta. The results of the study show that the level of effectiveness of hotel taxes in the city of Yogyakarta from 2017 to 20121 is very effective. The target trend and tax realization in 2020-2021 are down due to Covid-19, but the effectiveness trend is up in 2020 and 2021 because the target is lowered. For the contribution of hotel taxes to tourism sector revenue and Yogyakarta City PAD is relatively large, and is a mainstay source of PAD. Efforts to optimize hotel taxes carried out by the Yogyakarta City BPKAD include collecting taxpayer data, determining hotel taxes and carrying out hotel tax collection.